Peters' Anomaly. (January 2013) - Sault, Robert W.; Sheridan, Jeffrey
While conducting medical aid in Mozambique, a 41 year old African male presented to our eye clinic complaining of visual impairment. The male was found to have Peters' anomaly type 2, a rare congenital ocular malformation leading to sensory amblyopia and glaucoma.